3D Resistivity Data Modelling to Identify Aquifer Geometry by Qualitative Analysis (Field Study: PDAM Surabaya Groundwater Conservation Area, Pasuruan) - Ayi Syaeful Bahri; Amien Widodo; Widya Utama; Dwa Desa Warnana; Pegri Rohmat Aripin; Adib Banuboro; Robi Alfaq Abdillah (Institut Teknologi Sepuluh Nopember, 2017)
The resistivity method is one of the geophysical methods used to identify the aquifer layer by utilizing the rock response to the flow of electric current. This method considered more effective and can give a good subsurface cross-section, especially the fluid response. In this research, 3D modelling for identify geometry of subsurface geological structures of this study focus in three area (Plintahan, Duren Sewu, and Karangjati) using 2D resistivity data. Data Measurement of 2D resistivity using Wenner-Schlumberger configuration with length of each line is 155 meters and the target depth is 30 meters. The purpose of this configuration is to get an inverse with a resolution that is good to the lateral and vertical. The results show that the types of rocks in the research area was clay, sand and sandy shale with resistivity value 50-150 ohm-meter where sand rocks interpreted as aquifer rocks at depths of 2-7 meters and a thickness of 2-5 meters. The result of the resulting 3D modelling showed that the aquifer layer in Plintahan area showed the geological continuity with anticline geometry, in another area the aquifer layer in Durensewu - Karang Jati area showed the aquifer geometry prediction but there is no continuity of the structure of each other.